The economic benefits of a green building – Evidence from Malaysia - Dwaikat, Luay N. (Elsevier Ltd, 2018)
Due to significant environmental and economic benefits associated with reduced energy consumption in green buildings, energy efficiency is considered a key driver for the green building movement. However, factors related to the actual building performance and future energy prices highly impact the actual energy cost of a green building. This research evaluates the actual economic performance of a green building in use in term of energy consumption and examines how different scenarios for energy price inflation would affect the cost saving associated with reduced energy consumption in the building throughout its whole life cycle. Based on actual data record, it is found in the research that the investigated green building saves around 71.1% of energy compared to the industry baseline. From life cycle perspective, the green building saves around 5756 kW h/m2 which corresponds to $2,796,451 at 1% average annual increase in energy price and it is more than fourfold at 5% average annual increase in energy price and reaches around $12,107,060. This research provides an empirical evidence for the economic benefits associated with reduced energy consumption in the green building.